Penerapan MOORA pada Evaluasi Kinerja dalam Mengefektifkan Biaya Operasional - Arridha Zikra Syah; Yessica Siagian (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Sales performance evaluation is a stage in conducting an examination and assessment of information seeking performance or work results of employees / workers in the sales field of a company, this is done in an effort to streamline the company's operational costs because a salesperson is the peak in the achievement and turnover of an operational cost. company, carried out by a salesperson where a salesperson certainly sells products produced by the company or organization with a predetermined sales level, so it is necessary to conduct an assessment or evaluation of sales performance in order to appoint and find out the quality level of sales performance, to reward good sales performance will increase motivation and enthusiasm for sales work achievement so as to be able to streamline operational costs, a systemized selection is made using the MOORA (Multi-Objective Optimization On The Basis Of Ratio Analysis) method. in measuring sales performance evaluation so that the implementation process is more structured and runs honestly and fairly. The results obtained in the study that alternative A1 is a sales that has the best performance with a value of 0.546616.